Morfologia e produção de mudas de Dimorphandra gardneriana Tul. - Moura, Sueli da Silva-Santos (2016)
The description of the morphological structures of seeds, seedlings and young plants is important for the identification and recognition of the plant in the field, also using seedlings with high standard of quality is fundamental to the success of fields and it depends on the technologies used during production, among those factors the type and size of the container, the substrate and the light incidence influence on plant growth. With this, the objective was to study the morphology of seeds, germination, seedlings and young plants of Dimorphandra gardneriana Tul., and the influence of the container substrate and shading levels in the production of seedlings of this species. The experiments were carried out at the Laboratory of Seed Analysis (LSA), in a greenhouse and in the seedling nursery of the Department of Plant Science and Environmental Sciences at the Center of agricultural science of the Federal University of Paraíba – (CCA UFPB) in Areia Paraíba. In the experiment I it was described the external morphological characteristics of seeds: color, texture and consistency of the integument, form of seeds, positionof the hilum and micropyle, raphe and other structures present in addition to the internal characteristics of the embryo (cotyledon, hypocotyl axis - roots, plumule, central cylinder) and the presence of endosperm. Also in the germination study, which was considered from the primary root protrusion it was evaluated also the normal seedlings on the fifth day after sowing when there was root and hypocotyl to the production of protophilus while the young plant was characterized when the leaves were fully expanded, observing the color, roots (primary and secondary), lap hypocotyl, cotyledons, epicotyl and issued protophilus. The second experiment studied the influence of the container in the quality of seedlings and it was tested plastic bags, tubes and plastic bottles with different diameters. In the experiment III, the substrates used to assess the growth of seedlings were the commercial Basaplant®; vegetable soil; vegetable soil + sand in the proportions of 3:1, 1:1 and 1:3; vegetable soil + cattle manure in the proportion of 3:1, 1:1 and 1:3. To check the requirement of plants as the light intensity in the experiment IV it was used different levels of shading simulated with polyolefins screens black in color shading being the treatments at 0% shading (full sun) - T1, 30% - T2, 50 % - T3 and 70% shading - T4. The study of morphology is important in taxonomic studies for laboratory and nursery studies as well as natural regeneration. For production of D. gardneriana seedlings is recommended to use the dimensions of polyethylene bags 15 x 28 cm, the vegetable soil substrate and without shading.